2011
DOI: 10.1371/journal.pone.0028555
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase Inhibitor Dasatinib Induces a Marked Adipogenic Differentiation of Human Multipotent Mesenchymal Stromal Cells

Abstract: BackgroundThe introduction of specific BCR-ABL inhibitors in chronic myelogenous leukemia therapy has entirely mutated the prognosis of this hematologic cancer from being a fatal disorder to becoming a chronic disease. Due to the probable long lasting treatment with tyrosine-kinase inhibitors (TKIs), the knowledge of their effects on normal cells is of pivotal importance.Design and MethodsWe investigated the effects of dasatinib treatment on human bone marrow-derived mesenchymal stromal cells (MSCs).ResultsOur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 60 publications
1
24
1
Order By: Relevance
“…In a rat model of physiologic bone turnover, it has been shown to increase trabecular bone volume likely via inhibition of osteoclast activity, while not having a significant effect on osteoblast parameters, suggesting that dasatinib may 'dysregulate' bone remodeling (Vandyke et al 2010b). Another study has demonstrated direct MSC adipocyte differentiation at the expense of the osteoblast lineage (Borriello et al 2011). This finding raises the potential for dasatinib to contribute to skeletal fragility as has been demonstrated with another class of drug, thiazolidinediones, that preferentially direct osteoblast differentiation toward adipocytes and increase fracture risk (Bilik et al 2010).…”
Section: Effect On Bone Cells: Osteoclasts and Osteoblastsmentioning
confidence: 87%
“…In a rat model of physiologic bone turnover, it has been shown to increase trabecular bone volume likely via inhibition of osteoclast activity, while not having a significant effect on osteoblast parameters, suggesting that dasatinib may 'dysregulate' bone remodeling (Vandyke et al 2010b). Another study has demonstrated direct MSC adipocyte differentiation at the expense of the osteoblast lineage (Borriello et al 2011). This finding raises the potential for dasatinib to contribute to skeletal fragility as has been demonstrated with another class of drug, thiazolidinediones, that preferentially direct osteoblast differentiation toward adipocytes and increase fracture risk (Bilik et al 2010).…”
Section: Effect On Bone Cells: Osteoclasts and Osteoblastsmentioning
confidence: 87%
“…Primary cultures of fibroblasts were established as reported previously (8). Particularly, fibroblasts were obtained from: i) healthy subjects; ii) the patient identified in this study and his parents; and iii) two additional patients with Wolfram syndrome previously characterized in our departments.…”
Section: Primary Fibroblast Isolation and Cell Culturesmentioning
confidence: 99%
“…Cells were collected and resuspended in lysis buffer containing 1% deoxycolate, 1% Triton X-100, 0.1% SDS, 150 mM NaCl, and protease inhibitors (8,9), and incubated for 1 h at 4 8C. Samples were, then, centrifuged and the supernatants processed by immunoblotting in order to evaluate PARP cleavage.…”
Section: Staurosporine-induced Apoptosis and Protein Extractionmentioning
confidence: 99%
See 2 more Smart Citations